The reproductive biology and conservation of two rare Banksia species. - Barrett, Gregory J. (Curtin University, 1985)
Two rare Banksia species, B. chamaephyton A.S. George and B. elegans Meissner, were the subject of this study. B. chamaephyton is gazetted as rare under the Wildlife Conservation Act of Western Australia and B. elegans has been recorded by various authors as restricted in range and habitat.Data were collected on the distribution, habitat, reproduction and fire responses of each species. Both were found to occur predominantly in the Irwin Botanical District. B. chamaephyton is found in low heath on sand over laterite and B. elegans in scrub or thickets on deep, yellow sands. Data on species co-occurring with B. chamaephyton were gathered for the purpose of identifying habitats with actual or potential populations of the rare species. Several species appeared to be reliable indicators.Both species are represented in areas set aside for conservation although some populations are vulnerable and their loss would considerably reduce the range of each species. Of particular concern are the southernmost populations of B. chamaephyton and the northernmost populations of B. elegans. The latter appears to represent a size variant within the species. Although neither species is currently endangered, it is recommended that B. chamaephyton remain a gazetted rare species and that consideration be given to the gazettal of B. elegans.Both species are xenogamous and probably bird-pollinated although pollination by small mammals is a possibility. Both also have very low fruit and seed set. In B. chamaephyton, this is probably related to resource availability but B. elegans possesses a malformed stigma which may prevent the normal reproductive process from taking place. Most populations of B. elegans are sterile. Further research into the sexual reproduction and propagation of B. elegans is recommended.Fire is important to both species. In B. chamaephyton, fire, together with subsequent wet/dry cycles, is necessary for seed release from the follicles. Seedling recruitment is negligible in B. elegans. Mature individuals of both species survive fire and in B. elegans fire stimulates root suckering. Autumn burns appear to be most suitable for recruitment in both species, preferably at a minimum interval of ten years.